Teaching Classics in the Digital Age - Feuser, Stefan,Merten, Stephanie,Wesselmann, Katharina (Universitätsverlag Kiel | Kiel University Publishing, 2021)
The papers and videos presented here are the result of the international conference 'Teaching Classics in the Digital Age' held online on the 15 and 16 June 2020. As digital media provide new possibilities for teaching and outreach in Classics, the conference 'Teaching Classics in the Digital Age' aimed at presenting current approaches to digital teaching and sharing best practices by bringing together different projects and practitioners from all fields of Classics (including Classical Archaeology, Greek and Latin Studies and Ancient History). Furthermore, it aimed at starting a discussion about principles, problems and the future of teaching Classics in the 21st century within and beyond its single fields.
Keywords: Classics; Digital Humanities; Digital Learning; Archaeology; Ancient History; Greek and Latin Studies; Ancient World; Educational: History; Ancient history; Educational: Classical and ancient languages; Computer applications in the arts and humanities